Inequality in low- and middle-income countries: Does fiscal policy matter? - Magwedere, Margaret Rutendo; Marozva, Godfrey (The Economics and Finance Letters, 2025)
The main purpose of this article was to examine the link between tax revenue and income distribution in low- and middle-income countries. Reducing inequality is a central policy objective under the Sustainable Development Goals (SDGs). However, these countries deeply entrench inequality, and progress towards achieving optimal equality levels remains slow. The study, utilizing the system’s generalized method of moments, investigates the correlation between tax revenue and income inequality in a panel of African countries from 2010 to 2021. The findings indicate that for the countries in this study, an increase in tax revenue is associated with a rise in income inequality. Consequently, higher tax revenues tend to widen income disparities in the countries studied. Policymakers often employ various economic instruments to achieve equitable income distribution, with tax revenue being a critical tool for this purpose. However, the study reveals that increases in tax revenue do not necessarily filter to reduce income inequalities. Other factors, such as corruption control and regulatory quality, significantly influence the redistributive effects of tax revenue. These findings provide important insights for policymakers, highlighting the need for comprehensive strategies that address these additional factors to effectively reduce income inequality.